2015
DOI: 10.5812/ajdr.21202
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Teeth Development in Panoramic Radiograph and Skeletal Maturity in Lateral Cephalogram

Abstract: Background: Using a reliable indicator to identify different phases of skeletal maturation is an important issue in orthodontic diagnosis and treatment planning. Objectives: The aim of this study was to evaluate the correlation between stages of tooth calcification and cervical vertebral maturation in Iranian individuals. Patients and Methods: 216 digital panoramic and lateral cephalometry of healthy patients, 99 males and 117 females (aged 8 to 16 years) seeking orthodontic treatment included in the study. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The result of this study is similar to those of previous studies, revealing an association between tooth and cervical vertebral maturity in people without craniofacial anomalies. 1,2,3,11,12 Strong significant association between cervical vertebral maturity and tooth calcification stages in children aged 7 to 16 years old with cleft lip and palate may occur because both had normal condition and craniofacial anomalies had no effects, or because both cervical vertebrae and tooth had accelerated or delayed maturity. The development of mandibular second molar starts at the age of 3 years, the crown formation finishes at the age of 7 to 8 years, and the root formation finishes at the age of 14 to 15 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The result of this study is similar to those of previous studies, revealing an association between tooth and cervical vertebral maturity in people without craniofacial anomalies. 1,2,3,11,12 Strong significant association between cervical vertebral maturity and tooth calcification stages in children aged 7 to 16 years old with cleft lip and palate may occur because both had normal condition and craniofacial anomalies had no effects, or because both cervical vertebrae and tooth had accelerated or delayed maturity. The development of mandibular second molar starts at the age of 3 years, the crown formation finishes at the age of 7 to 8 years, and the root formation finishes at the age of 14 to 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…1 Dental and skeletal age can be seen on panoramic and lateral cephalometric radiographs. 2 Both are frequently connected with each other in several researches; one of them shows strong correlation between dental and skeletal age. 3 According to 2013 Indonesia Basic Health Research, cleft lip and palate cases were estimated to be found in 0.08% of the total number of children in Indonesia.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations